Social Media and Content Analysis Critical Discourse Analysis of Kuali Merah Putih Episode 3 Content on Bobon Santoso's YouTube Channel - Rifal Ramadhan; Khaerudin Imawan; Rahmayanti (Jurnal Informasi dan Teknologi, 2025)
The content of the Red and White Cauldron video on the Bobon Santoso YouTube Channel on March 5, 2024, is entitled "Justice Is Not Here! Merah Putih Muyu Tribe, Boven Digoel. It conveyed an interesting message by raising issues among the people of South Papua. The intentions, goals, and discourses captured in the culinary content reflect sentiments and feelings about the state of the people of South Papua through materials, including cooking activities. This study aims to analyse three aspects of the conversation: text structure, social cognition, and social context. The analysis of the critical discourse of Teun A. Van Dijk was used in this study. Auditory observation and documentation procedures are used to examine the data after the dialogue of the episode is transcribed. The analysis findings reveal a text structure built on micro, super, and macro structures. These structures support the overall discussion and include stylistic, syntactic, rhetorical, and semantic components. The social cognition analysis explores the situation of the people of South Papua, which is part of the Republic of Indonesia, from various perspectives. And in the social context, this analysis conveys that the problem in South Papua has existed for a long time and has not been seriously resolved by the Government.